THERMAL EVAPORATION PROCESSES OF CHALCOGENIDES UNDER VACUUM CONDITIONS (E Global Congress, 2024)
This study investigates the thermal evaporation processes of chalcogenide compounds in vacuum environments. Chalcogenides, known for their unique optical and electronic properties, are increasingly used in semiconductor technologies and thin-film applications. The research focuses on the mechanisms of evaporation, material deposition, and the influence of vacuum conditions on film quality and uniformity. Through detailed analysis, we examine the impact of temperature, pressure, and deposition rates on the resulting thin films, providing insights into optimizing these parameters for improved performance. The findings contribute to advancements in the fabrication of high-quality chalcogenide-based materials for applications in optoelectronics, photovoltaics, and thermoelectric devices.